Characterization of salt tolerant wheat genotypes by using morpho-physiological, biochemical, and molecular analysis - Irshad, Ahsan; Ahmed, Rana Imtiaz; Ur Rehman, Shoaib; Sun, Guozhong; Ahmad, Furqan; Sher, Muhammad Ali; Aslam, Muhammad Zahid; Hassan, Mohamed M.; Qari, Sameer H.; Aziz, Muhammad Kashif; Khan, Zulqurnain (Frontiers in Plant Science, 2022)
Food security is facing a major threat from salinity and there is a need to develop salt tolerant crop varieties to ensure that the demand for food from the world’s increasing population is met. Salinity mostly occurs in arid and semi-arid regions. It may cause many adverse physiological effects on plants, i.e., toxic ion accumulation, disturbed osmotic potential, and decreased crop yield. The present study aimed to investigate the morphological, physiological, biochemical, and genetic parameters of wheat genotypes under salt stress. Six wheat genotypes were screened for salt tolerance at the seedling and maturity stage. Seeds were sown at 0 and 150 mM of salinity level. Biochemical traits, i.e., shoot/root fresh and dry weight, chlorophyll a/b and total chlorophyll contents, shoot nitrogen, shoot phosphorus, proline, and carbohydrates were measured. Wheat genotypes showed a significant increase in free amino acids, shoot nitrogen, and total soluble proteins under saline conditions. Higher Na+/K+ ratio and free amino acids were estimated under 150 mM NaCl treatment in Pasban-90 and found to be the most salt-tolerant genotype. By contrast, reduced proline, total chlorophyll, and Na+/K+ ratio were found in Kohistan-97 marking it to be sensitive to stress. Expression analysis of HKTs genes was performed to validate the results of two contrasting genotypes. The differential expression of HKT2; 1 and HKT2; 3 explained the tissue and genotype specific epigenetic variations. Our findings indicated that these selected genotypes can be further used for molecular studies to find out QTLs/genes related to salinity. This suggests that, in contrasting wheat genotypes, there is a differentially induced defense response to salt stress, indicating a functional correlation between salt stress tolerance and differential expression pattern in wheat.